2011
DOI: 10.3844/ajmsp.2011.35.39
|View full text |Cite
|
Sign up to set email alerts
|

Strains of <i>Klebsiella Pneumoniae</i> from Intensive Care Unit Producing CTX-M-15 Extended Spectrum Beta Lactamases

Abstract: Problem statement: Resistance to third generation cephalosporins due to acquisition and expression of Extended Spectrum β-Lactamase (ESBL) among Gram-negative bacteria is on the increase. Infections involving extended spectrum beta lactamase bacteria are associated with significant morbidity and mortality. Therefore, infections due to ESBL isolates continue to pose a serious challenge to infection management worldwide. Since screening for ESBL is not a common practice in hospitals in Enugu state, this study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…were imipenem, ciprofloxacin, norfloxacin, gentamicin and kanamycin (100% each).The superiority of flumequine and gentamicin for the in vitro action in Klebsiella pneumoniae was reported by Sarathbabu et al (2012), who reported that all tested strains of Klebsiella pneumoniae were highly sensitive to gentamicin and flumequine. Also, Iroha et al (2011) reported that all isolated Klebsiella pneumoniae subsp. pneumoniae strains were highly sensitive to enrofloxacin and norfloxacin.…”
Section: Discussionmentioning
confidence: 99%
“…were imipenem, ciprofloxacin, norfloxacin, gentamicin and kanamycin (100% each).The superiority of flumequine and gentamicin for the in vitro action in Klebsiella pneumoniae was reported by Sarathbabu et al (2012), who reported that all tested strains of Klebsiella pneumoniae were highly sensitive to gentamicin and flumequine. Also, Iroha et al (2011) reported that all isolated Klebsiella pneumoniae subsp. pneumoniae strains were highly sensitive to enrofloxacin and norfloxacin.…”
Section: Discussionmentioning
confidence: 99%
“…For DDST, amoxicillin-clavulanic acid, AMC (20/10µg) was placed at the center of the Mueller-Hinton (MH) agar plate, and CTX (30µg) and CAZ (30µg) disk were each placed at a distance of 15mm from the central disc (AMC). The plates were incubated at 37 o C for 18-24 h. ESBL production was inferred phenotypically when the zones of inhibition of CAZ or CTX were expanded by AMC 2,4 .…”
Section: Test For Colistin Resistance and Esbl-mentioning
confidence: 99%
“…showing less susceptibility to any third-generation cephalosporins (e.g., CAZ, CTX) according to the CLSI protocol were phenotypically defined as ESBL bacteria 2,4,20 . ESBL bacteria were screened for ESBL genes ( bla TEM, bla SHV, bla CTX-M, bla Oxa) using conventional PCR.…”
Section: Pcr Screening For Esbl Genes: Bacteriamentioning
confidence: 99%
See 2 more Smart Citations